S39 Endogenous circulating BMP9 maintains endothelial barrier function. (December 2018) - Li, W; Long, L; Yang, X; King, R; Southwood, M; Tong, Z; Caruso, P; Upton, PD; Salmon, RM; Condliffe, AM; Nourshargh, S; Chilvers, ER; et al.
Abstract : Introduction and objective: Heightened endothelial cell permeability is a feature of life-threatening conditions such as sepsis and acute respiratory distress syndrome. However, there is a lack of pharmacological therapies targeting this pathological hyper-permeability. Bone morphogenetic protein 9 (BMP9) is a circulating vascular quiescence factor, signalling on vascular endothelial cells (ECs) through activin receptor-like kinase 1 (ALK1) and BMP receptor type II (BMPRII). Since recombinant BMP9 affords protection from endothelial permeability induced by inflammatory mediators, our objective was to investigate whether endogenous BMP9 plays a constitutive role in maintaining endothelial barrier function. Methods: Wild-type mice were treated with BMP9 neutralising antibody at 5 mg/kg to assess: 1) rapid vascular leak using live imaging in mouse cremaster muscle and 2) more sustained vascular leak using Evans Blue extravasation, neutrophil accumulation and lung histology. Changes in endogenous BMP9 during LPS-induced endotoxemia were assessed by mRNA expression in the liver and protein levels in circulation. Anti-BMP9 effects on endothelial VE-cadherin were assessed by immunostaining. BMP9 signalling on EC receptors was profiled using microarray. Effects of BMP9 administration were investigated using an intranasal LPS-induced lung injury model. Results: Selective inhibition of circulating BMP9 alone resulted in a rapid (<5 min) increase in vascular permeability. Additional effects of specific BMP9 neutralisation included interstitial lung oedema and neutrophil extravasation. Circulating BMP9 levels were decreased markedly in murine endotoxemia, with a temporary reduction in hepatic BMP9 mRNA expression and cleavage of BMP9 by plasma proteases. BMP9 neutralisation led to a rapid loss of VE-cadherin junction in ECs; whereas BMP9 signalling in ECs effectively suppressed AQP1 and KDR expression, both important mediators of vascular permeability. Pharmacological administration of BMP9 prevented vascular leak and histological evidence of acute lung injury induced by LPS. Conclusions: Endogenous circulating BMP9 plays a constitutive role in maintaining lung endothelial barrier function. Remarkably, inhibition of BMP9 alone was sufficient to increase lung vascular permeability and promote neutrophil extravasation. The reduction in circulating BMP9 associated with LPS-induced inflammation, and the rescue of lung permeability with exogenous BMP9 suggests that supplementation of this factor may be a useful therapeutic approach in conditions associated with lung endothelial injury.